2006
DOI: 10.1007/s11249-005-9007-2
|View full text |Cite
|
Sign up to set email alerts
|

Dry sliding tribological behavior of nanocrystalline and conventional polycrystalline copper

Abstract: Dry sliding tribological behavior of an electro-deposited nanocrystalline Cu (nc Cu) and a conventional coarse-grained Cu (cg Cu) has been investigated using a ball-on-disc tribometer with cemented tungsten carbide ball as the counterface. Experimental results showed that the wear resistance of copper with the nanocrystalline microstructure was enhanced relative to the coarsegrained form. The steady-state friction coefficient of the nc Cu was obviously lower than that of the cg Cu when the load is below 20 N. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…3b). Although many experimental studies [24,25] have confirmed the formation of ultra-refine or NC structure in the worn surfaces of ductile materials, obvious grain boundaries of large Ni 3 Al particles are not observed after wear test at 2 N in this study, indicating that grain refinement or nanocrystallization is not likely to occur on the worn surface after a sufficiently long period of dry sliding operation (960 m). However, it should be emphasized that a wearinduced layer is clearly observable at the top of the worn surface.…”
Section: Wear Analysiscontrasting
confidence: 67%
“…3b). Although many experimental studies [24,25] have confirmed the formation of ultra-refine or NC structure in the worn surfaces of ductile materials, obvious grain boundaries of large Ni 3 Al particles are not observed after wear test at 2 N in this study, indicating that grain refinement or nanocrystallization is not likely to occur on the worn surface after a sufficiently long period of dry sliding operation (960 m). However, it should be emphasized that a wearinduced layer is clearly observable at the top of the worn surface.…”
Section: Wear Analysiscontrasting
confidence: 67%
“…Oxidational wear is the most common chemical wear process [3,6], in which a thin oxide layer prevents the bonding between the asperities as well as metal-metal contact. The oxide can be a result of diffusion controlled oxide growth or agglomeration of oxide/oxidized debris/inclusion of oxide/oxygen into highly disrupted surface regions [11,12]. After critical thickness, it can lead to delamination at the metal/oxide interface [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For Cu, the attemps to reduce wear and the friction force includes grain refinement [12][13][14][15], presence of oxide film/depris, tribolayer or mechanically mixed layer (MML) [5,[12][13][14][16][17][18][19][20], as well as alloying, and DS [4,5,[19][20][21][22][23]. The tribological behaviour of nano-and coarse-grained Cu has been studied in [12][13][14][15]. It was shown that in ballon-disk oscillating tests with 5 N load against WC-Co balls the wear loss was four times higher for c-Cu (coarse-Cu) than for nc-Cu (nano-Cu), the respective CoFs being 0.74 and 0.54.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, tribological properties of nanostructured materials have been paid more attention and many experimental results have shown a significant enhancement in friction and wear properties of nanostructured materials, e.g. [1][2][3][4][5]. However, it should be mentioned that most investigations on wear properties of nanostructured materials have been focused on sliding wear mode.…”
Section: Introductionmentioning
confidence: 99%